Integration of Big Data in Port Logistics as a potentiator of competitiveness and productivity - Viloria-Vilarete, Eliecer E. (EFIM Ediciones, 2022)
The purpose of this article was to analyze the Integration of Big Data in Port Logistics, from the topic of its ability to enhance the competitiveness and productivity of maritime ports.Method: A systematic review of information was carried out in reference databases for the search of scientific, review, and reflection articles, as well as books and degree works or thesis that dealt with the subject in the period of time between 2012 and 2022.. Results: As results, 28 documentary sources were obtained that provided relevant analyzes and considerations on the logistics task, specifically on port logistics, as well as on 4.0 technology and on Big Data. Conclusions: The high relevance of the integration of Big Data in Port Logistics as an enhancer of competitiveness, productivity and sustainability of organizations traditionally known as ports was evidenced.